2011
DOI: 10.5032/jae.2011.03064
|View full text |Cite
|
Sign up to set email alerts
|

Competency Modeling in Extension Education: Integrating an Academic Extension Education Model with an Extension Human Resource Management Model

Abstract: The purpose of this study was to compare and contrast an academic extension education model with an Extension human resource management model. The academic model of 19 competencies was similar across the 22 competencies of the Extension human resource management model. There were seven unique competencies for the human resource management model. The integration of the models was informative to support and confirm the educational directions of each model. The human resource management model provided information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…Amongst the recommendations by authors in human resource management and extension professionals for organisations to be effective in the 21st century is improved competency (Scheer et al, 2011citing Stern & Kemp, 2004 Vol. 44, No.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the recommendations by authors in human resource management and extension professionals for organisations to be effective in the 21st century is improved competency (Scheer et al, 2011citing Stern & Kemp, 2004 Vol. 44, No.…”
Section: Discussionmentioning
confidence: 99%
“…Given trends such as changing and complex conditions and other pressures organizations are facing, if organizational leaders want to be proactive in managing their human capital, it is important for them to apply current information on trends and the implications those trends may have on work in the organization to their planning and support of human capital. The research reported here is the first step in a larger research process (Cochran, 2009;Scheer, Cochran, Harder, & Place, 2011) where OSU Extension is applying research on trends and implications to identify and promote competencies needed for organizational success.…”
Section: Congruence Between Thementioning
confidence: 99%
“…Professionalism, as demonstrated by indepth knowledge of subject matter and intensive preparation-manifested in instructional skills, as well as a thorough understanding of the scholarly and scientific principles underlying such skills and methods-are the hallmark of an agricultural extension officer's competence (Department of Agriculture, 2005). Therefore, extension educators must develop technical expertise and educational process skills to meet the changing needs of clientele (Ghimire & Martin, 2011;Gibson & Hillison, 1994;Scheer, Harder, & Place, 2011;Seevers, Graham, & Conklin, 2007). Extension professionals must possess personal strengths, capabilities as an educator, capabilities in information technology, and expertise in their academic specialty.…”
Section: Introductionmentioning
confidence: 98%